1966
DOI: 10.1177/00220345660450063201
|View full text |Cite
|
Sign up to set email alerts
|

The Dissolution Kinetics of Hydroxyapatite in the Presence of Kink Poisons

Abstract: Le addition de phosphates exerceva nulle influentia super le rapiditate del dissolution. Sub conditiones de un vigorose convection fortiate, le emanation de iones ab sitos de defectos superficial pareva restringer le intensitate del dissolution. Alora le addition de phosphates organic e inorganic reduceva le rapiditate del dissolution per un factor de inter 2 e 8, e iste phenomenon esseva attribute a absorption a sitos de defectos superfical.Phenomenologically, tooth decay is simply the dissolution of enamel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1970
1970
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…How ever, fluoride present in the buffer solu tion at I ug/ml did reduce the dissolution rate by 20-30%, and this is consistent with numerous reports in the literature [Napper and Smythe, 1966;Forward, 1977;AponteMerced and Feagin, 1979;Grenby and Bull, 1980]. Tung el al., [1981] recently de monstrated exchange of F" for OH" at the surface sites of apatite, and this is consist ent with the observations and mechanism proposed here.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…How ever, fluoride present in the buffer solu tion at I ug/ml did reduce the dissolution rate by 20-30%, and this is consistent with numerous reports in the literature [Napper and Smythe, 1966;Forward, 1977;AponteMerced and Feagin, 1979;Grenby and Bull, 1980]. Tung el al., [1981] recently de monstrated exchange of F" for OH" at the surface sites of apatite, and this is consist ent with the observations and mechanism proposed here.…”
Section: Discussionsupporting
confidence: 89%
“…Other workers have suggested that the dissolu tion of non-carbonated hydroxyapatite and dental enamel is diffusion controlled [StralJ'ors, 1958;Gray. 1962;Napper and Smythe. 1966;Higuchi et al, 1969;Linge and Nancollas, 1973;White and Nancollas, 1977].…”
Section: Discussionmentioning
confidence: 99%
“…3, 4) although no categorical statement on the rate orders could be made it appeared to be first for calcium and sec ond for phosphorus with respect to undersa turation. Napper and Smythe [1966], how ever, using a porous disc found the dissolu tion of hydroxyapatite as measured by weight to be second order.…”
Section: Discussionmentioning
confidence: 97%
“…Attempts to synthesize mixed-metal hydroxylapatites in the binary series Ca -Cd, Ca -Pb, Ca -Sr and Cd -Pb followed a method adapted from that of Valsami-Jones et al (1998) and Napper and Smythe (1966). A 300 ml solution of 1.3 M ammonium acetate was prepared, heated in a water-bath to 90ºC and the pH adjusted to 7.5 using ammonia solution.…”
Section: Metal Phosphate Synthesismentioning
confidence: 99%